Modelling the nesting-habitat of the Cinereous Vulture Aegypius monachus on a fine scale for conservation purposes - Guerrero-Casado, Jose; Arenas, Rafael; Tortosa, Francisco S. (BIRD STUDY, 2013)
Capsule Nests of Cinereous Vultures were found to be located farther from roads, villages and the edge of large vegetation patches. They preferred large vegetation patches containing extensive Cork Oak cover on steeper slopes and with lower solar radiation. Less than 8% of the study area was predicted to be suitable for nesting.Aims To generate a predictive habitat suitability map for the Cinereous Vulture's nesting-habitat on a fine scale for conservation applications within its breeding range.Methods Habitat features of 43 nest-locations and random points were compared in order to identify nest-habitat selected in the region of the Hornachuelos Natural Park (Spain). A logistic regression approach was used to create habitat models.Results Compared with random points, nests were found to be located farther from roads, villages and patch edges, and in large vegetation patches containing extensive Cork Oak cover on steeper slopes with lower solar radiation. The predictive map revealed that less than 8% of the study area had a greater probability of occupancy than 0.8.Conclusions Most habitats in the study area are unsuitable for nesting suggesting that conservation of the best suitable areas is important. The fine-scale predictive map approach may be valuable in designating conservation priority areas.
APSAPSThe following values have no corresponding Zotero field: pub-location: 4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND publisher: TAYLOR & FRANCIS LTD
Keywords: Capsule nests; Cork oak; habitat modelling; Spain